Answers

2015-06-13T22:17:44+05:30
The terms are n - 2, 4n -1 and 5n + 2.
We know that if a , b and c are in A.P. then  \frac{a+c}{2} =b
i.e. average of a and c is equal to b.
Therefore, by the condition:
 \frac{(n-2)+(5n+2)}{2} =4n - 1.
 \frac{n-2+5n+2}{2} =4n -1
 \frac{6n}{2} =4n-1
⇒3n=4n-1
⇒4n-3n=1
⇒n=1
Ans:The value of n is 1 and the numbers are 1-2 = -1 , 4*1-1=3 and 5*1+2 = 7 respectively as we see that -1+4=3 and 3+4=7.
===============================================
Please mark as the best.
1 5 1